Microvideo Neurofeedback-Oriented Approach in Science Subjects for Grade IV Elementary Students - Gunawan, I Kadek arya; Adrianus I Wayan Ilia Yuda Sukmana; Alexander Hamonangan Simamora (Universitas Pendidikan Ganesha, 2025)
The use of innovative learning media is crucial in creating an engaging, interactive, and effective learning process. There is a growing need for media that can enhance students' active engagement through the integration of neurofeedback elements. This study aims to develop neurofeedback-oriented animated micro-videos for the Science and Social Studies (IPAS) subject in fourth-grade elementary school. The method employed is Research and Development (R&D) using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of three experts (in content, media, and instructional design), three students for the individual trial, six students for the small group trial, and 28 fourth-grade students in the field trial through pre-test and post-test procedures. Data were collected through interviews, questionnaires, and expert validations. The validation results showed that the material and media aspects received a feasibility score of 98%, while the instructional design component received 95%, all categorized as